F.I.T. Closet Translation Tool and Written Reflection - Bauman, Taylor (My University, 2023)
My Honors Project focused on creating a translation tool for the volunteers at the F.I.T. Closet in Manhattan to utilize when helping Spanish-speaking shoppers. Using my semester's experience volunteering as a Spanish interpreter at the F.I.T. Closet (during Fall 2022), collaborating with the coordinator, the English-speaking volunteers, and Spanish-speaking shoppers at the F.I.T. Closet, and researching and comparing similar materials, I created translations of Spanish words and phrases that would facilitate communication for these different linguistic groups. In a written response, I give background information about the project, detail what I learned while volunteering at the F.I.T. Closet, reflect on how my experience at the F.I.T. Closet shaped my decisions in the production of the translation tool, explain how my research on other materials influenced the design of the tool, consider some of the difficulties during the process, and share what I have discovered during the community-based learning experience.